Extraction of equivalent noise source model from photovoltaic systems - Prajapati, Manish (2019)
Photovoltaic (PV) systems have become popular as one of the renewable energy sources in recent years. With increasing number of PV systems, potential electromagnetic interference (EMI) issues from the PV systems cannot be ignored. In order to evaluate the EMI potential of a PV system, an in-circuit measurement method to extract its equivalent common-mode and differential-mode noise source models is described and validated. These noise source models serve as black boxes for further EMI analyses.